Trends of formula feeding practices among infant and young children in Bhubaneswar city - Raj, Rishav; Behera, B K (Indian Journal of Child Health, 2016)
Objective: To assess the formula feeding practices in Bhubaneswar city and the parameters influencing it. Materials and Methods: A cross-sectional study was conducted from January 1, 2014, to December 31, 2014, in OPD and well-baby clinic of Hi-Tech Medical College, Bhubaneswar and pharmacies in the different Bhubaneswar Municipal Corporation units of this city. 250 mothers having infants and young children were interviewed individually as per pre-designed questionnaire. A separate set of questionnaires for 33 pharmacies were interviewed separately. The data were analyzed by SPSS 16.0 software. Results: About 38% of the mothers were preparing formula with proper dilution. 47% of mothers were adhering to a single brand. Formula sellingconstitutes 15-20% of the average total monthly income of pharmacies. 83% of the formulas were sold without prescription. Pharmacist (30%) and media (20%) were the major influencing factors. Conclusion: Mothers should be clearly explained about the health hazards of formula feeding during antenatal visits and subsequent immunization visits. Infant milk substitute act should include pharmacists, druggists, and chemists.